Hubungan Karakteristik Ibu dengan Pemakaian Kontrasepsi IUD di Desa Tolang Jae - ., Ayannur; Rangkuti, Nuraliyah (Universitas Aufa Royhan, 2019)
Family planning is an effort to regulate child birth, distance and ideal age of childbirth, manage pregnancy through promotion, protection and assistance in accordance with reproductive rights to create quality families. This research is an observational analytic study using a cross sectional design which is a research design in which independent variables and dependent variables are measured and collected at the same time. The population in this study were all PUS mothers (Fertile Age Couples) who were in Tolang Jae village in 2018 as many as 199 people. Sampling using Slovin formula, as many as 90 people. Data collection techniques using a questionnaire, and then performed univariate, bivariate analysis using the chi-square test and multivariate analysis using multiple logistic regression tests. The results of this study indicate that the chi-square statistical test obtained on the age variable with a value of p = 0.001 ; education variable with a value of p = 0.002; and knowledge variable with p value = 0.014 <0.05, which means there is a relationship between age, education and knowledge with the use of IUD contraception in Tolang Jae Village, Sayurmatinggi District, South Tapanuli Regency in 2018.